Advanced preclinical testing of a design-optimized ceramic bearing for a cervical total disc replacement - Lucia Kölle; Gregory Pryce; Andrew R. Beadling; Michael Bryant; Richard M. Hall; Stephen J. Ferguson; Benedikt Helgason (PLoS ONE, 2026)
Objective Arthroplasty in the cervical spine is performed using Total Disc Replacement (TDR) implants. This study investigates the safety and tribology of a design-optimized ceramic TDR bearing. Methods Samples of an optimized bearing geometry were manufactured from the bioceramic BIOLOX ® delta (CeramTec GmbH, Germany) and tested in a six degree of freedom universal joint simulator in diluted calf serum at body temperature. The investigated load and motion profiles simulated movements of daily living; three pure rotations under static load and three rotations coupled under sinusoidal load as well as adverse events (three subluxation test conditions). Results Dynamic coefficients of friction during flexion/extension and lateral bending were µ = 0.16 ± 0.011 and µ = 0.16 ± 0.070, respectively. Friction factors during flexion/extension and lateral bending were f = 0.14 ± 0.0092 and f = 0.13 ± 0.063, whereas the friction factor in axial rotation was f = 0.033 ± 0.0028 and for three coupled rotations under sinusoidal load, it was f = 0.13 ± 0.028. The design demonstrated a sufficient resistance against subluxation, with subluxation forces more than 3.5-fold the 20N that are typically required as acceptance criteria in FDA safety and effectiveness data. Conclusion Friction values were found to be comparable to or higher than those typically reported for ceramic-on-ceramic hip replacements. Furthermore, the results indicated that the optimized bearing design is sufficiently resistant to subluxation. Significance: Test protocols to investigate safety and tribology of cervical TDRs are proposed and their results are reported for a design-optimized ceramic TDR bearing.